Association between lifestyle factors and depressive symptoms among Chinese middle school students: a cross-sectional study. Issue 10 (26th November 2021) - Ren, Zheng; Wang, Qi; Xiong, Wenjing; Fan, Xinwen; Guo, Xia; Ma, Juan; He, Minfu; Shen, Yue; Zhou, Ge; Gong, Ping; Liu, Meitian; Yang, Xiaodi; et al.
ABSTRACT: This study aimed to identify the independent contributions of lifestyle factors to depressive symptoms among Chinese middle school students, with a focus on gender differences. A cross-sectional study of 3081 middle school students was conducted in Ganzhou City, Jiangxi Province, China. Students were asked to complete a questionnaire including socio-demographics, lifestyle factors, the Pittsburgh Sleep Quality Index and the Chinese Secondary School Students Depression Scale. The total prevalence of depressive symptoms was 19.9%. Poor quality of sleep, smoking, drinking and longer mobile phone use time were related to increased prevalence of depressive symptoms after adjusting for potential confounders. A significant interaction between gender and quality of sleep on the depressive symptoms was found ( P = 0.014). The gender-stratified analysis showed that quality of sleep was significantly associated with depressive symptoms in both genders. However, the effect in males was greater than that in females.